2011
DOI: 10.1590/s0100-69162011000100017
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento do feijoeiro sob o uso de biofertilizante e adubação mineral

Abstract: A produção intensiva de alimentos exige manejo adequado do solo para garantir a produtividade e a sustentabilidade ambiental. Uma das alternativas é a utilização de resíduos orgânicos no desenvolvimento das culturas, diminuindo a dependência de adubos minerais. Com o objetivo de avaliar o desenvolvimento da cultura de feijão (Phaseolus vulgaris L.), utilizando biofertilizante e adubação mineral, conduziu-se o experimento com seis tratamentos dispostos ao acaso, em esquema fatorial, em quatro blocos, com parcel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 8 publications
(7 reference statements)
2
15
0
9
Order By: Relevance
“…Similar positive effects of bio-fertilizers on yield and growth of pearl millet as well as various field crops, compared to mineral fertilizers, has been well documented (e.g. Galbiatti et al, 2011;Bana et al, 2012;Abdullahi et al, 2014;Patel et al, 2014) . In her investigation to the effect of mineral, organic, and bio-fertilizers on yield and agronomic characteristics of pearl millet Shandaweel 1 cultivar, Hend (2017) reported that the application of nitrobine bio-fertilizer in combination with 60 kg N fed -1 gave similar results to the application of 120 kg N fed -1 alone, for the yield and the studied agronomic characteristics.…”
Section: Cultivar X Fertilizer Interactionsupporting
confidence: 55%
“…Similar positive effects of bio-fertilizers on yield and growth of pearl millet as well as various field crops, compared to mineral fertilizers, has been well documented (e.g. Galbiatti et al, 2011;Bana et al, 2012;Abdullahi et al, 2014;Patel et al, 2014) . In her investigation to the effect of mineral, organic, and bio-fertilizers on yield and agronomic characteristics of pearl millet Shandaweel 1 cultivar, Hend (2017) reported that the application of nitrobine bio-fertilizer in combination with 60 kg N fed -1 gave similar results to the application of 120 kg N fed -1 alone, for the yield and the studied agronomic characteristics.…”
Section: Cultivar X Fertilizer Interactionsupporting
confidence: 55%
“…Meanwhile, both Luqueño et al (2010) and Galbiatti et al (2011) reported that, application of organic fertilizers resulted in higher productivity by common beans than did mineral fertilizers. Additionally, increases in common bean productivity when manure is used for fertilizer have been reported by several authors (PAULETTI et al, 2008;CAVALCANTE et al, 2009;MELO et al, 2009;PEREIRA et al, 2013;PEREIRA et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Resultados semelhantes foram obtidos por Luqueño et al (2010) e Galbiatti et al (2011), nos quais foi possível observar efeito positivo da adubação orgânica em comparação aos fertilizantes minerais no feijoeiro. Outros estudos têm evidenciado aumentos na produtividade do feijão comum com o uso de estercos na adubação, sendo relatados por vários autores (PAULETTI et al, 2008;CAVALCANTE et al, 2009;MELO et al, 2009;PEREIRA et al, 2013;PEREIRA et al, 2015).…”
Section: Resultsunclassified
“…Galbiatti et al [36], studying the common bean (Phaseolus vulgaris (L.)) under biofertiliser and mineral fertiliser, found that there was a statistical difference between the mean values under study for productivity only.…”
Section: Source Of Variationmentioning
confidence: 99%